Autosegmentation of prostate anatomy for radiation treatment planning using deep decision forests of radiomic features - Macomber, Meghan W; Phillips, Mark; Tarapov, Ivan; Jena, Rajesh; Nori, Aditya; Carter, David; Folgoc, Loic Le; Criminisi, Antonio; Nyflot, Matthew J (Physics in Medicine & Biology, 2018)
Machine learning for image segmentation could provide expedited clinic workflow and better standardization of contour delineation. We evaluated a new model using deep decision forests of image features in order to contour pelvic anatomy on treatment planning CTs.